The productivity of Sahel goats and sheep under transhumant management in Northern Burkina Faso - Wilson, R.T. (1988)
Results of a 2-year study on goats and sheep in northern Burkina Faso are reported. In both goats and sheep, females comprised more than 75% of flock numbers. Intervals between parturitions in goats were 312 days overall but were significantly affected by the season of the previous birth: in sheep the interval was 280 days, this also being affected by season. There were 1.08 kids born per litter in goats and 1.06 lambs in sheep: litter size in sheep differed significantly between seasons and between years of parturition. Kids weighed 12.8 kg at 150 days, there being differences due to season and parity: lambs weighed 14.9 kg, this weight being affected by season, parity and litter size. Seasonal variations in weights of adult female goats and sheep were marked, being about 12% below the overall annual average weight for each age class in June (end of dry season) and 12% above the mean in November (post rains). Annual productivity was 22.1 kg of live young per breeding goat per year, 874 g per kg of breeding goat per year and 2.08 kg per kg metabolic weight of breeding goat per year. The corresponding figures for sheep were 23.8 kg, 806 g and 2.01 g. Season had the most important influence on productivity but this was also affected by parity in sheep.